Assessment of Jawbone Density at Potential Implant Sites in Posterior Edentulous Mandible Using Cone Beam Computed Tomography (CBCT) on a Selected Group of Yemeni Population - Al-hashedi, Ahmed Ali Ali (University of Science and Technology, Sana’a, 2026)
The present study analyzed 81 CBCT scans of Yemeni adults in posterior edentulous mandibles, consisting of 41 males (50.6%) and 40 females (49.4%). Participants ranged from 41 to 80 years old, with a mean age of 59.4 ± 10.63 years. The mean of bone density to each implant sites was 1370 ± 317 HU, corresponding mainly to D1 bone quality according to Misch’s classification. this study reported a significant gender difference was observed, with males demonstrating higher mean bone density (1498 ± 394 HU; D1) compared to females (1238 ± 525 HU; mostly D2) (P < 0.0001). The distribution of bone density between the right and left sides of the posterior mandible showed no statistically significant differences. Our study showed bone density in the right side was 1376 ± 430 HU at implant Site-1 (S1) and 1348 ± 538 HU at potential implant Site-2 (S2), with a P-value 0.7942, while the left side demonstrated that the mean bone density was 1385 ± 450 HU at potential implant Site-1 (S1) and 1369.9 ± 499 HU at potential implant Site-2 (S2), with a P-value 0.9648. A consistent and highly significant pattern of lingual bone density over the buccal bone density of implant site was identified. In Site-1, lingual density measured 1539.9 ± 361 HU compared to 1221 ± 454 HU buccally (P < 0.0001), additionally, in Site-2 lingual bone reached 1618.6 ± 357 HU versus 1099.3 ± 526 HU buccally (P < 0.0001). Overall, there was a statistically significant difference between lingual bone density (1579 ± 361 HU) compared to buccal density (1160 ± 495 HU), (P < 0.0001), indicating denser lingual cortical structures of implant site, Bone density differences were larger in Site-2, particularly at the apex, demonstrating greater structural disparity in posterior mandibular regions. Analysis of the implant-site levels (neck, body, apex) showed a progressive decline in buccal bone density from neck to apex in both regions. In Site-1, buccal values were 1484 HU (neck), 1161 HU (body), and 1019 HU (apex), all significantly different. In Site-2, buccal density declined from 1526 HU to 966.5 HU and 805.8 HU. In contrast, the finding results demonstrated statistically significant differences in bone density between three points (neck, body, and apex) at potential implant sites (S1 & S2) at the buccal zone (P < 0.0001), while there was no significant difference in bone density between the same three points at the lingual zone. In our study the differences between Site-1 and Site-2 regions showed significantly higher buccal bone density (1221 HU) in Site-1 compared to buccal bone density in Site-2 (1099 HU), P = 0.0353. While there was no significant difference between lingual1 (1540 HU) and lingual2 (1619 HU), P = 0.2974, However, a clear difference was observed between them. reflecting thicker lingual cortical bone morphology and lesser trabecular bone density in the Site-2 region in comparation to site 1. in the Site-2 region. Sex-specific analysis demonstrated that males consistently exhibited higher bone density than females in most implant levels. In the buccal region, significant differences were found at body and apex levels (P < 0.0001), while neck levels (compact bone density) showed no meaningful variation. In addition, our study showed significantly higher density at the body in the lingual region in males (1681 HU) compared to females (1535 HU), p-value = 0.0083. while neck and apex levels showed no significant differences. This higher pattern of bone density in males was consistent across both Site-1 and Site-2, particularly at the body and apex regions.
Keywords: Jawbone Density; Cone Beam Computed Tomography; Oral Surgery; Implantology; Sana'a